Cultural diversity in today's diverse world - United Nations Development Programme (New York : Published [for] the United Nations Development Programme, 2004)
This report carefully examines and rejects claims that cultural differences necessarily lead to social, economic and political conflict or that inherent cultural rights should supersede political and economic ones. Instead it offers some concrete ideas on what it means in practice to build and manage the politics of identity and culture in a manner consistent with the bedrock principles of human development.
Includes notes and bibliographic notes.
Includes bibliographical references: p. 112-124.
ne 11/06/2021
Ref
Keywords: Multiculturalism